The Enhancing Corporate Responsibility in Unlawful Termination Through Administrative Sanctions - Sembogo, Achmad Dimas Aliffian; Suherman, Suherman (Law Development Journal, 2025)
This research examines the legal responsibility of companies conducting unlawful termination of employment in Indonesia, focusing on Supreme Court Decision No. 47 K/Pdt.Sus-PHI/2025 (Irwanto v. PT Perkebunan Milano). The study aims to analyze the extent to which Indonesian law ensures the fulfillment of workers’ rights through judicial decisions and to explore the urgency of adding administrative sanctions for companies that coerce or misclassify employee resignations. Using a normative juridical research method combined with statutory, case, and comparative approaches, this study relies on primary legal materials, including the Manpower Law, the Job Creation Law, Government Regulation No. 35 of 2021, and relevant court rulings. Data were analyzed qualitatively through descriptive and analytical interpretation of legal norms and judicial reasoning. The findings show that the Supreme Court recognized the company’s unlawful conduct and ordered the payment of severance and compensation to the worker, yet the decision did not impose further sanctions that could deter similar violations. From the perspective of Hans Kelsen’s Liability Theory, legal responsibility arises only when sanctions accompany a breached obligation, while Cesare Beccaria’s Deterrence Theory emphasizes that punishment must create preventive and corrective effects. The analysis reveals a structural weakness in Indonesia’s labor law enforcement, which focuses on restitution rather than deterrence. The novelty of this research lies in proposing the integration of administrative sanctions—such as fines, license suspension, or compliance audits—as a complement to judicial remedies, thereby ensuring stronger accountability and sustainable protection of workers’ rights.